DANCES ON THE EDGES OF MODERNISM - Basuki, Ribut (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
When modernism started to become the major paradigm in the western world, western theatre also took part in the development. Realism, a child of modernism, soon became the mainstream of the theatrical expression. As soon as realism became established in the first-half of the 20th century, anti-realist movements flourished as reactions to the establishment. These movements were so diverse that it ranged from movements which were purely artistic such as what was done by Edward Gordon Craig until those that were political like what was proposed by Bertolt Brecht (1992).